Peningkatan Pengetahuan dan Kepatuhan Diet Hipertensi melalui Pendidikan Kesehatan di Posyandu Lansia Tlogosuryo Kota Malang - Hilda Mazarina Devi; Rona Sari Mahaji Putri (Jurnal Akademika Baiturrahim Jambi, 2021)
Chronic hypertensive disorder in geriatry may trigger other serious cardiovasculary diseases. The aim of this study was to determine the effectivity of health education on geriatry knowledge and adherence on hypertension diet in Posyandu Lansia Tlogosuryo, Malang. Using pre-experimental within a one group pre-post test design, 30 elderly on chronic hipertensive disorder recruited as a sample of the study. At the baseline, less than a half of participant (46.7%) had good and fair knowlegde level and only 43.3% showed high adherence on hipertension diet. After a series of health education, 70% of participant showed an improvement on knowledge level and 50% showed higher adherence on hypertension diet. The results of paired t-test showed a p value of  0.003; 0.000 < 0.05 on the knowledge level and diet adherence level, respectively. Conclusion: Health education was effective to increase the knowledge and diet adherence among geriatry with chronic hipertensive disorder